Terpenoids from Kiwi endophytic fungus Bipolaris sp. and their antibacterial activity against Pseudomonas syringae pv. actinidiae - Yu, Jun-Jie; Wei, Wen-Ke; Zhang, Yu; Cox, Russell J.; He, Juan; Liu, Ji-Kai; Feng, Tao (Frontiers in Chemistry, 2022)
A chemical investigation on the kiwi endophytic fungus Bipolaris sp. resulted in the isolation of eight new terpenoids (1–8) and five known analogues (9–13). Compounds 1–5 are novel sativene sesquiterpenoids containing three additional skeletal carbons, while compounds 4 and 5 are rare dimers. Compounds 6–8 and 13 are sesterterpenoids that have been identified from this species for the first time. Compounds 4 and 5 showed antibacterial activity against kiwifruit canker pathogen Pseudomonas syringae pv. actinidiae (Psa) with MIC values of 32 and 64 μg/mL, respectively.